MAG School Teachers' Attitudes toward Practitioner Research in English Language Classrooms in Sharjah - Genc, Emine (2010)
A Master of Arts Thesis in Teaching English to Speakers of Other Languages (TESOL) by Emine Genc Entitled, "Mag School Teachers' Attitudes toward Practitioner Research in English Language Classrooms in Sharjah," May 2010. Available are both Hard and Soft Copies of the Thesis.